Dampak Ekonomi Kejadian Avian Influenza di Kabupaten Pinrang pada Peternakan Ayam Petelur - Ardilasunu Wicaksono; Sri Wahyuni; Agik Suprayogi (JURNAL KAJIAN VETERINER, 2026)
Avian influenza reduces egg production in layer chickens, leading to significant economic losses for farmers. Pinrang, one of the largest egg-producing regions in South Sulawesi, continues to face recurring cases of avian influenza. This study aimed to estimate the economic losses associated with avian influenza incidences in layer chicken farms in Pinrang District. The economic impact was assessed using partial analysis by calculating both direct and indirect costs of avian influenza at the district and farm levels on an annual basis. Input parameters included epidemiological and economic data obtained from the Department of Livestock and Plantation of Pinrang District, scientific literature, commodity and veterinary product records, and veterinary practitioners. Sensitivity analysis was performed to evaluate the effect of uncertain parameters on the estimated outcomes. The results indicated that the total economic loss reached IDR 12.4 billion/year at the district level and IDR 9 million/year at the farm level. The largest allocation of the losses was attributed to reduced egg production (38.1%), followed by vaccination costs (25.9%). The most influential parameters affecting the estimates were disease incidence and egg prices. In conclusion, avian influenza causes substantial economic losses in Pinrang District, highlighting the importance of preventive measures to minimize future costs.